Verification of social media content for news production: a thematic review of journalistic technique and strategies - Melinda Baharom,; Akmar Hayati Ahmad Ghazali,; Abdul Muati@Zamri Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
News organisations increasingly use social media content for breaking news, eyewitness accounts and user-generated videos. However, the veracity of such content is often questioned as social media platforms are prone to false reports, rumours and manipulation. This highlights the importance of journalists using robust verification techniques and strategies to ensure the accuracy and reliability of social media content in their reporting. However, prior research revealed no review papers discussing patterns of verification techniques and strategies journalists use on social media content for news production. This thematic review aims to synthesise literature from 2019 to 2023 on the journalist's strategies and techniques in verifying social media content for news production using a thematic review (TR). A list of keywords (journalistic techniques and strategies used in verifying social media content for news production) related to the scope of this research was identified. In the second step, the keyword was searched for studies in Scopus, Dimensions and Mendeley, and 31 papers were reviewed. A thematic review was carried out, where five final themes were identified: traditional techniques, combination strategies, technology and social media tools, computational tools and training, and media literacy. This study will benefit knowledge of journalists' verification social media techniques and strategies and future study of journalists' verification practices.